Muslim Children’s English Class: An Innovation Of Thematic Islamic-Based English Learning for Young Learners - Grahmayanuri, Novria; Aminuddin; Efrina Nasution, Linda; Khawardy, Lucy; Syam Nasution, Fadhillah; Suna Hasibuan, Isra; Yusriani, Nida; Sitorus, Nadrah; Andiyani Batubara, Efira; Arnita Pulungan, Nina (Education and Talent Development Center of Indonesia, 2025)
This community service project aims to develop an innovative model of English language learning for young Muslim learners by integrating Islamic values into thematic instructional materials. The initiative responds to the need for culturally and religiously relevant English education in early childhood settings. Through a participatory action approach, the project designed storybooks, illustrated vocabulary cards, Islamic-themed songs, and activity worksheets, and implemented them in collaboration with local Islamic learning centers. The materials focused on themes such as the Five Pillars of Islam, daily prayers, good manners (akhlaq), and Prophet stories. Results showed increased vocabulary acquisition, active engagement from children, and improved teaching confidence among educators. This model offers a replicable and sustainable approach to promoting both language development and moral education simultaneously. The project contributes to the growing field of culturally responsive pedagogy and provides practical resources for educators seeking to integrate language instruction with faith-based values.